Analysis of electromagnetic phenomena in modulated flux synchronous generator. Issue 5 (3rd September 2018) - Jedryczka, Cezary; Szelag, Wojciech; Gwozdz, Michal Jan; Krystkowiak, Michal
Abstract : Purpose: The purpose of this paper is to present the electromagnetic phenomena in permanent magnet synchronous generator (PMSG) suited for wind turbines with uniquely designed system of two windings. The machine's windings allow for application of a reliable and low-cost power electronic converter. Design/methodology/approach: The 2D field-circuit model has been developed and used in comparative analysis between reference design PMSG with concentrated three-phase winding and two-windings PMSG to facilitate application of a low-cost and reliable AC/DC power electronic converter. The paper focuses on comparison of radial force density, core losses and torque waveforms in the proposed and reference machine with sinusoidal load currents. Findings: The usefulness of the proposed approach for analysis of the two-winding PMSG performance by means of the field-circuit model has been proved. The obtained results show practically no drop off of performance of proposed machine in relation to reference PMSG. Moreover, it has been shown that both machines are characterized by the same level of radial force density. Therefore, the lower cost and reliable power electronic converts can be applied in the wind power energy systems (WPES) by slightly more complex design of the stator winding. Originality/value: The proposed 2D field-circuit numerical model makes it possible to analyze the performance of the star-delta winding PMSG dedicated to be loaded by the AC to DC converter specially designed to achieve high reliability and efficiency of the system. Presented comparative studies on generator performance show that proposed modulated synchronous flux generator characterize with the same output torque at given supply current and core losses level like conventional PMSG with sinusoidal load.